Intravascular large B-cell lymphoma of the kidney: A case report - Jia Nan; Wang Guobao; Wan Liyan; Li Xiao; Bai Xiaoyan; Geng Jian (BMC, 2011)
Abstract We report a 41-year-old Chinese woman with intravascular large B-cell lymphoma diagnosed by percutaneous renal biopsy. The patient was admitted to Nanfang Hospital of Southern Medical University, Guangzhou, China with complaints of high spiking fever for a month and bilateral lower limb fatigue with difficulty ambulating for the past 5 months. She had renal dysfunction with a total urinary protein of 5.61 g/dL (56.1 g/L), serum albumin of 2.89 g/dL (28.9 g/L), urea nitrogen of 2.24 mg/dL (1.6 mmol/L), and serum creatinine of 0.54 mg/dL (48 μmol/L). Bone marrow biopsy revealed myeloproliferative disorder without abnormal myeloid or lymphocytic proliferation. Positron Emission Tomography-Computed Tomography (PET-CT) showed marked bilateral swelling and enlargement of the renal parenchyma with splenic enlargement and involvement of multiple vertebrae. Percutaneous renal biopsy showed island-like accumulations of medium to large lymphoid cells in many areas of the interstitium, with round vesicular nuclei containing distinct basophilic nucleoli. Immunohistochemical analysis together with other supportive investigation confirmed the diagnosis of intravascular large B-cell lymphoma. Ten days later, she was started on chemotherapy with CHOP (cyclophosphamide, doxorubicin, leurocristime and prednisone) for a week. Palliative radiotherapy DT 40Gy/20F with other supportive treatment was provided for metastatic foci in the medullary cavity of the sternum, T1-T7. The patient regained muscle strength in both lower limbs and was able to walk again after three weeks. The patient was discharged after hepatic and renal function and proteinuria values had returned to normal. Follow-up data shows the patient to be alive nine months after discharge.